Efficacy and safety of omalizumab in patients with chronic urticaria who exhibit IgE against thyroperoxidase - Maurer, Marcus; Altrichter, Sabine; Bieber, Thomas; Biedermann, Tilo; Bräutigam, Matthias; Seyfried, Stefan; Brehler, Randolf; Grabbe, Jürgen; Hunzelmann, Nicolas; Jakob, Thilo; Jung, Andreas; Kleine-Tebbe, Jörg; et al. (The journal of allergy and clinical immunology, 2011)
Background - A subgroup of patients with chronic spontaneous urticaria (CU) exhibits IgE antibodies directed against autoantigens, such as thyroperoxidase (TPO). We conducted this study to investigate whether such patients with CU with IgE against TPO benefit from treatment with omalizumab, a humanized anti-IgE mAb licensed for the treatment of severe persistent allergic (IgE-mediated) asthma. - Objectives - We sought to assess the efficacy of omalizumab treatment in patients with CU with IgE autoantibodies against TPO. - Methods - In this multicenter, randomized, double-blind, placebo-controlled study patients with CU (male/female, 18-70 years of age) with IgE autoantibodies against TPO who had persistent symptoms (wheals and pruritus) despite standard antihistamine therapy were randomized to receive either omalizumab (75-375 mg, dose determined by using the approved asthma dosing table) or placebo subcutaneously once every 2 or 4 weeks for 24 weeks. The primary end point was the change from baseline in mean weekly urticaria activity score after 24 weeks of treatment, as calculated from patients’ diaries. The safety and tolerability of omalizumab were also assessed. - Results - Of the 49 randomized patients (omalizumab, n = 27; placebo, n = 22), 42 completed the study. At week 24, patients demonstrated a mean reduction in the weekly urticaria activity score from baseline of 17.8 with omalizumab and 7.9 with placebo (P = .0089). Complete protection from wheal development was observed in 19 (70.4%) patients in the omalizumab group compared with only 1 (4.5%) patient in the placebo group. The rate of adverse events was similar in both groups. - Conclusions - The results of this study indicate that omalizumab is an effective treatment option for patients with CU with IgE autoantibodies against TPO who are refractory to conventional treatment.